Pengelolaan Perguruan Tinggi Sebagai Organisasi Nirlaba - Nur Rulifatur Rohmah; idam mustofa (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2022)
College is a non-profit organization whose ultimate goal orientation is not to earn and accumulate profits, but college is a servant and community service. Universities are classified into two parts, namely government universities and non-government (private) universities. Strategic management of universities, both government and non-government, goes through the following stages: 1. Strategy analysis known as SWOT analysis. 2. Strategy formulation in general, unit and functional. 3. Strategy implementation. 4. Strategy evaluation. Financial reporting Non-profit organizations are divided into two for accounting non-profit entities, regulated in PSAK No. 45 concerning the financial reporting of non-profit organizations issued by the Indonesian Institute of Accountants. Meanwhile, the government's non-profit entity accounting is guided by Law no. 17 of 2003 concerning the management of state finances, Government Regulation No. 6 of 2004, Government Accounting Standards, and of course also on SAK-PSAK No. 45.